Antihyperglycemic activity of oil palm Elaeis guineensis fruit extract on streptozotocin-induced diabetic rats = Aktiviti antihiperglisemik minyak ekstrak buah kelapa sawit Elaeis guineensis ke atas tikus diabetik Teraruh Streptozotocin - Sharif, Mohd. Faez; Hamid, Muhajir; Ismail, Amin; Adam, Zainah (Penerbit Universiti Kebangsaan Malaysia, 2015)
Hypoglycaemic and antihyperglycemic activity of oil palm Elaeis guineensis fruit extract on normal and Streptozotocin-induced diabetic rats was studied. The oil palm fruit extract (OPF) were administered orally at different concentrations (100, 200 and 500 mg kg-1 b.w.) in fasting and post-prandial rats. Hypoglycaemia was not observed in the group of normal rats treated with OPF. In fasting rats, OPF (500 mg kg-1 b.w.) has caused the blood glucose level (BGL) to reduce significantly. For post-prandial diabetic rats, the antihyperglycemic activity was observed after OPF treatment at concentrations 200 and 500 mg kg-1. Chronic OPF treatments (for 28 days) had increased the diabetic rat’s body weight and reduced BGL as well as improved plasma insulin secretion. The result of this study suggests E. guineensis palm fruit extract show evidence of antihyperglycemic properties from the reduction of the BGL in diabetic rats.